The Battle of Mohács - Pap, Norbert, (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
The story of the battle of Mohács and of King Louis II's dramatic escape, only to meet his end by falling from his horse and drowning in the stream of Csele, is well-known. These traumatic events have been seen as symbolizing the fall of the independent Hungarian Kingdom and the dawn of an age of oppression. This volume presents new research on these events and their interpretation, focusing on topics such as battlefield reconstruction, troop involvement, firearm use, and later political use and abuse of the memory of the battle. Contributors are Pál Fodor, Péter Gyenizse, Erika Hancz, Máté Kitanics, Sándor Konkoly, Dénes Lóczy, Tamás Morva, Norbert Pap, Júlia Papp, Gábor Szalai, and Gábor Varga.